2017
DOI: 10.1111/jch.12970
|View full text |Cite
|
Sign up to set email alerts
|

The science of salt: A regularly updated systematic review of salt and health outcomes (December 2015–March 2016)

Abstract: The purpose of this review was to identify, summarize, and critically appraise studies on dietary salt relating to health outcomes that were published from December 2015 to March 2016. The search strategy was adapted from a previous systematic review on dietary salt and health. Overall, 13 studies were included in the review: one study assessed cardiovascular events, nine studies assessed prevalence or incidence of blood pressure or hypertension, one study assessed kidney disease, and two studies assessed othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 37 publications
2
39
1
4
Order By: Relevance
“…A priority is to develop minimum methodologic standards for the conduct of validation studies. A regularly updated systematic review of the literature assessing the association of sodium intake to clinical outcomes found the majority of studies could not meet even minimum methodologic criteria . The initial TRUE consortium position on blood pressure measurement in research studies was also developed because few research studies used the recommended methods to assess blood pressure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A priority is to develop minimum methodologic standards for the conduct of validation studies. A regularly updated systematic review of the literature assessing the association of sodium intake to clinical outcomes found the majority of studies could not meet even minimum methodologic criteria . The initial TRUE consortium position on blood pressure measurement in research studies was also developed because few research studies used the recommended methods to assess blood pressure .…”
Section: Discussionmentioning
confidence: 99%
“…A regularly updated systematic review of the literature assessing the association of sodium intake to clinical outcomes found the majority of studies could not meet even minimum methodologic criteria. [69][70][71][72][73][74] The initial TRUE consortium position on blood pressure measurement in research studies was also developed because few research studies used the recommended methods to assess blood pressure. 13 Institutions funding research, journals, and scientists need to carefully assess the validity of the methods used in research relating to dietary sodium to ensure reliable guidance to public health programs.…”
Section: Setting Recommendationmentioning
confidence: 99%
“…Up to May 2015, we annually published a summary of studies on salt and health outcomes . In June 2015, we replaced the annual reviews with regularly published summaries that include risk of bias assessments and critical appraisals . From June 2015 to July 2016, 64 studies were identified that met our inclusion criteria, ie, original human research on salt intake and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While our body requires a certain amount of salt to work properly, too much of it is bad for health. A report summarizing 13 studies from eight countries concluded that a high salt diet is closely related to cardiovascular events (Wong et al, ). According to the Centers for Disease Control and Prevention (CDC), most Americans consume too much sodium in their daily diet, with a current average of 3.4 g/d.…”
Section: Introductionmentioning
confidence: 99%